Answer:
The statement that is true in every aspect regarding his claim is:
- False, because when combined in this manner, the alternating signs of the series are lost ( Wyatt ignored the negative in the first factor)
Explanation:
The series is given as:
![\sum_(n=0)^(3) (-(1)/(3))^n\cdot 9](https://img.qammunity.org/2020/formulas/mathematics/middle-school/th9jq0q3wyjd8myk2kbte41v71uzpm10s3.png)
which could also be written by:
![\sum_(n=0)^(3) (-(1)/(3))^n\cdot 9=\sum_(n=0)^(3) (-(1)/(3))^n\cdot 3^2\\\\\\\sum_(n=0)^(3) (-(1)/(3))^n\cdot 9=\sum_(n=0)^(3) (-1)^n((1)/(3))^n\cdot 3^2](https://img.qammunity.org/2020/formulas/mathematics/middle-school/koxe5l8t6ddo2j2h6bgyl27nus8yzox0j5.png)
i.e.
![\sum_(n=0)^(3) (-(1)/(3))^n\cdot 9=\sum_(n=0)^(3) (-1)^n\cdot 3^(-n)\cdot 3^2\\\\\\\sum_(n=0)^(3) (-(1)/(3))^n\cdot 9=\sum_(n=0)^(3) (-1)^n\cdot 3^(2-n)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/mxu8eyu5xp95g7tfa0a9rnrquqtg9pxj47.png)
which is not equivalent to:
![\sum_(n=0)^(3) 3^(2-n)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/kdop3ffri01jqr8jptjedcyw56l3b62dbs.png)
Since, on expanding the actual series we get the sum as:
![\sum_(n=0)^(3) (-(1)/(3))^n\cdot 9=(-(1)/(3))^0\cdot 9+(-(1)/(3))^1\cdot 9+(-(1)/(3))^2\cdot 9+(-(1)/(3))^3\cdot 9\\\\\\=9-(1)/(3)* 9+(1)/(3^2)* 9-(1)/(3^3)* 9\\\\\\=9-3+1-(1)/(3)\\\\\\=(22)/(3)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/kzi1e7onao4ky0ucfxr5xuj7qazlupmgxf.png)
Now, the expansion of:
is:
![\sum_(n=0)^(3) 3^(2-n)=3^2+3^1+3^0+3^(-1)\\\\\\=9+3+1+(1)/(3)=(40)/(3)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/rt44568t75t6ylu7d0tf9fofckbv2du2rr.png)